Perlindungan Hukum Dan Pemenuhan Hak Korban Dalam Kasus Kecelakaan Lalu Lintas Yang Menyebabkan Korban Meninggal Dunia: Studi Kasus Di Pengadilan Negeri Kupang Kelas 1 - Rinaldy Herchion Asanab; Rudepel Petrus Leo; Heryanto Amalo (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Traffic accidents resulting in fatalities in Kupang City based on BPS Kupang City data series have increased in the period 2020-2022. In general, traffic regulations are regulated by Law No. 22 of 2009 on Road Traffic and Transportation. Victims who die due to road accidents have rights that must be fulfilled and passed on to their heirs. For this reason, legal protection of the rights of victims who die as a result of traffic accidents is necessary. This research uses empirical legal research, namely legal research that functions to examine how the law works in a community environment, in this case conducted at the Kupang District Court Class 1. Data collection techniques are carried out through interviews, observation and documentation and then analyzed descriptively and qualitatively. The results showed that: (1) The fulfillment of the rights of victims of death in cases of traffic accidents in Kupang City, is in accordance with applicable laws and regulations if through legal channels, while in practice are used more family channels, so that the rights of victims are neglected. (2) The ideal form of legal protection for victims of death in cases of traffic accidents in Kupang City is repressive, namely: a) criminal sanctions, b) compensation, and c) government compensation.